A Novel Strategy to Simplify the Procedures in Treating Complicated Coronary Bifurcation Lesions: From a Bench Test to Clinical Application - Li, Dongdong; Ma, Wenshuai; Liu, Pengyun; Liu, Hao; Bai, Baobao; Zhang, Mingming; Guo, Wangang (Frontiers in Cardiovascular Medicine, 2022)
Background: Although provisional stenting strategy based on jailed balloon side branch (SB) protection is currently the standard approach for high-risk bifurcation lesion, its complexity still gives rise to procedure complications. We proposed a novel strategy, the jailed balloon proximal optimization technique (JB-POT), to simplify the procedures in treating complex coronary bifurcation lesions (CBLs). The present study was designed to verify the safety and efficacy of JB-POT under bench testing and clinical circumstances. Methods: The JB-POT procedure was performed on 10 samples of a silicone bifurcation bench model, and optical coherence tomography (OCT) was utilized to evaluate stent deployment. From December 2018 to July 2021, a total of 28 consecutive patients with true CBLs treated with JB-POT were enrolled. Immediate procedure results were observed, and clinical follow-ups were performed. Results: The bench test showed that JB-POT did not induce significant stent malapposition, underexpansion or distortion, as indexed by the malapposition rate, minimum stent area (MSA), eccentricity index and symmetry index determined through OCT. Under clinical circumstances, JB-POT did not induce significant malapposition, underexpansion or distortion. Among the 30 lesions, there was no primary endpoint event defined as side branch (SB) occlusion, need to rewire the SB with a polymer-covered guide wire, or failure to retrieve a jailed wire or balloon. One rewiring event and 0 double stenting events occurred as secondary endpoint events. One patient died of heart failure in the 8th month after discharge. Conclusions: The JB-POT protocol, which tremendously simplifies the current standard provisional stenting procedure, shows acceptability in safety and efficacy. Hence, it might become an applicable strategy for treating high-risk bifurcation lesions, especially those with multiple risked SBs.